2017
DOI: 10.1039/c7dt00269f
|View full text |Cite
|
Sign up to set email alerts
|

B–H functionalization of the monocarba-closo-dodecaborate anion by rhodium and iridium catalysis

Abstract: The regioselective derivatization of the monocarba-closo-dodecaborate anion via catalytic B-H bond activation is reported. Amide directing groups in combination with rhodium and iridium catalysts allowed for the direct functionalization of cage boron vertices. Products comprising B-C, B-N and B-Cl bonds were synthesized. As a key intermediate of the B-H activation step, an iridium complex with a direct B-Ir interaction was isolated and fully characterized by spectroscopic methods as well as X-ray crystallograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 119 publications
1
19
0
Order By: Relevance
“…Lavallo's group observed that reaction of palladium precursor 3 with chlorobenzene afforded products 4 and 5 in a 9:1 ratio, 5 probably being the product of 4 via elimination of benzene . Studies in our laboratory on the directing group‐assisted B–H activation of the [CB 11 H 12 ] – anion showed that amides 6 and 8 can selectively be transformed to iridium complexes 7 and 9 . In the present work we describe the preparation of rhodium and palladium complexes of 6 , which were isolated in high yields and fully characterized.…”
Section: Introductionmentioning
confidence: 82%
“…Lavallo's group observed that reaction of palladium precursor 3 with chlorobenzene afforded products 4 and 5 in a 9:1 ratio, 5 probably being the product of 4 via elimination of benzene . Studies in our laboratory on the directing group‐assisted B–H activation of the [CB 11 H 12 ] – anion showed that amides 6 and 8 can selectively be transformed to iridium complexes 7 and 9 . In the present work we describe the preparation of rhodium and palladium complexes of 6 , which were isolated in high yields and fully characterized.…”
Section: Introductionmentioning
confidence: 82%
“…Remarkably, the acid chloride 20 was inert to moisture and could be stored under ambient conditions for several months (Scheme A) . The use of these amide directing groups in combination with iridium and rhodium catalysts enabled direct functionalization of the B2–6 vertices to give B−X (X=C, N, Cl) bonds (Scheme B) . As a key intermediate of B−H activation, an iridium complex [Et 4 N] ⋅24 with a direct B−Ir interaction was isolated; the B−Ir bond was converted to a B−X bond, and the product 25 was fully characterized by X‐ray crystallographic analysis (Scheme C) …”
Section: Recent Advances In Synthetic Chemistry At the Boron Verticesmentioning
confidence: 99%
“…Recently,w eh ave developed broad methodology for monocarborane functionalization, [21] which will allow variation of the polyhedral boron moiety as af uture control element for modulating and investigating the structural as well as opticalproperties of metal acetylides. We have shown that control of the stoichiometry and nature of auxiliary ligands allows for a tuning of the structure and photophysical features.…”
Section: Full Paper Conclusionmentioning
confidence: 99%
“…Our systems exhibit intriguingr oom-temperature photoluminescence across the visible spectrum in gradient colors from blue to deep red. Recently,w eh ave developed broad methodology for monocarborane functionalization, [21] which will allow variation of the polyhedral boron moiety as af uture control element for modulating and investigating the structural as well as opticalproperties of metal acetylides.…”
Section: Full Paper Conclusionmentioning
confidence: 99%